Exploring Poverty Distribution: Islamic Legal Perspectives on the Categories of Fakir and Miskin - Febriandika, Nurrizqi; Yulitasari, Nadya Sukma; Sriploid, Tipmanee (Milkiyah: Jurnal Hukum Ekonomi Syariah, 2024)
The Indonesian government offers various assistance programs aimed at supporting underprivileged families, including Program Keluarga Harapan (PKH) and Bantuan Pangan Non Tunai (BPNT). In Islamic context, the concept of poverty is categorized into eight asnaf (groups), one of which is the poor. Within this category, two specific terms used are fakir and miskin, both of which describe individuals experiencing poverty but differ in their degree of need. This study aims to analyse the distribution of fakir and miskin individuals, based on data from the Keluarga Penerima Manfaat (KPM) recipients of the PKH and BPNT programs across five sub districts in Boyolali Regency. Utilizing a survey methodology, the study employs the SAGIS application to conduct an interpretative analysis and identify the beneficiaries in these areas. A total of 785 KPMs, who receive aid from the PKH and BPNT programs, were surveyed across the five sub districts. Of these, 209 KPMs (26.7%) were categorized as fakir, 294 KPMs (37.4%) were classified as miskin, and the remaining 282 KPMs (35.9%) did not fall into either category.